Mechanical properties of carving wax with various Ca-bentolite filter composition - Widjijono Widjijono; Purwanto Agustiono; Dyah Irnawati (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2009)
Background: The carving wax is used as a medium in dental anatomy study. This wax composes of many waxes and sometimes a filler is added. Carving wax is not sold in Indonesian market. Whereas the gradients of carving wax such as beeswax, paraffin and bentonite are abundant in Indonesia. Based on that fact, to make high quality and standard,the exact composition if this carving wax should be known. Purpose: The aim of this study was to investigate the effect of carving wax composition with Ca-bentonite filler on the melting point, hardness, and thermal expansion. Methods: Five carving wax compositions were made with paraffin, Ca-bentonite, carnauba wax, and beeswax in ratio (% weight): 50:20:25:5 (KI), 55:15:25:5 (KII), 60:10:25:5 (KIII), 65:5:25:5 (KIV), 70:0:25:5(KV). All components were melted, then poured into the melting point, hardness, and thermal expansion moulds (n = 5). Three carving wax properties were tested: melting point by melting point apparatus; hardness by penetrometer; thermal expansion by digital sliding caliper. The data were analyzed statistically using One-Way ANOVA and LSD0.05. Result: The Ca-bentonite addition influenced the melting point and thermal expansion of carving wax with significant differences between KI and other groups (p < 0.05). Ca-bentonite addition influenced the carving wax hardness and the mean differences among the groups were significant (p < 0.05). Conclusion: Ca-bentonite filler addition on the composition of carving wax influenced the physical and mechanical properties. The carving wax with high Ca-bentonite concentration had high melting point and hardness, but low thermal expansion.